2011
DOI: 10.1063/1.3615784
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry and Fermi level movement during the self-cleaning of GaAs by trimethyl-aluminum

Abstract: The removal of the native oxides from NH4OH-cleaned p-GaAs (100) by exposure to trimethyl-aluminum (TMA) was studied by in situ photoelectron spectroscopy using synchrotron radiation. The reduction of high-valence As- and Ga-oxides occurred through different routes: while As3+ was reduced to As(1±Δ)+ suboxides (with 0 ≤ Δ ≤ 1), Ga3+ was directly removed. The surface Fermi level was shifted by about 100 meV towards the valence band edge upon TMA exposure. This indicates that removing the native oxide of GaAs by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 24 publications
7
51
0
Order By: Relevance
“…Similar results were also found on In x Ga 1-x As (0<x<1) (100) surfaces [28,29]. Also Tallarida et al [30] reported the reduction of Gaand As-oxides by ALD of Al 2 O 3 (TMA/H 2 O). Ga 3+ states were completely removed.…”
Section: Passivation Of the Iii/v Gate Stack: Going Beyond Interface supporting
confidence: 81%
“…Similar results were also found on In x Ga 1-x As (0<x<1) (100) surfaces [28,29]. Also Tallarida et al [30] reported the reduction of Gaand As-oxides by ALD of Al 2 O 3 (TMA/H 2 O). Ga 3+ states were completely removed.…”
Section: Passivation Of the Iii/v Gate Stack: Going Beyond Interface supporting
confidence: 81%
“…While there are reports of arsenic oxides "bubbling" through an ALD HfO 2 overlayer, no such observations have been made for gallium oxides. 9 As a result we have to assume that such diffusion processes occur through 2−4 nm thick Ta 50 have demonstrated that the first two TMA pulses reduce the vast majority of the As 3+ surface species into As suboxides that are subsequently removed from the interface. Contrary, for the Ga 3+ oxides, they observe a slower and almost linear reduction of the species intensity for the first six pulses.…”
Section: ■ Discussionmentioning
confidence: 99%
“…TMA), known as the "clean-up" or "self-cleaning" effect. (3)(4)(13)(14)(15)(16)(17) In this mechanism, the metal precursor interacts with the native oxide by binding with oxygen, which is used to form the desired deposited oxide. For instance, Milojevic et al used in-situ XPS to investigate the reduction of native oxide of In 0.2 Ga 0.8 As during the ALD of Al 2 O 3 and showed that, upon the first TMA exposure, Al 2 O 3 was formed through the reduction of the As-and Gabased oxides, particularly the 3 + oxidation state.…”
Section: Interfacial Layer Evolution During Ald Of Al 2 O 3 On Inpmentioning
confidence: 99%